Answer:
- 36
Step-by-step explanation:
First evaluate g(18), then substitute the value obtained into h(x), then substitute the value obtained here into f(x).
g(18) = = = 6, then
h(6) = | 4(6) | - 12 = | 24 | - 12 = 24 - 12 = 12, then
f(12) = - 3(12) = - 36
-4t
4t
-10t
10t
The simplification of the expression 5t + (t - 3) - [(7t + 5) - (8 - 3t)] using PEMDAS rule is -4t.
Thus, option 1 is correct.
A method of reducing an expression, equation, or problem to a more concise or straightforward form is referred to as simplification.
Initially the small bracket then curly brackets and at last large brackets are required to solve according to the laws of simplification using PEMDAS rules.
The given expression can be simplified as:
5t + (t - 3) - [(7t + 5) - (8 - 3t)]
5t+t-3-[7t+5-8+3t]
5t+t -3-7t-5+8-3t
-4t
The simplification of the expression 5t + (t - 3) - [(7t + 5) - (8 - 3t)] is -4t.
Thus, option 1 is correct.
Learn more about expression here:
#SPJ6